Implementation of Position Equalization Policy at the Domestic Policy Strategy Agency of the Ministry of Home Affairs - Rinandhinka Yorinka Astrawaty; Hyronimus Rowa; Megandaru Widhi Kawuryan (Sean Institute, 2025)
This thesis discusses the Implementation of the Job Equivalency Policy at the Domestic Policy Strategy Agency of the Ministry of Home Affairs (BSKDN Kemendagri). BSKDN Kemendagri is an Echelon I Work Unit within the Ministry of Home Affairs that is affected by job equivalency in accordance with the regulation of PermenPANRB Number 17 of 2021 concerning the Equivalency of Administrative Positions into Functional Positions. The purpose of this study is to determine the implementation of the job equivalency policy at BSKDN Kemendagri along with the factors inhibiting the implementation and efforts of BSKDN Kemendagri to optimize the implementation of the job equivalency policy. The theory used in this study is the conception of Merilee S. Grindle (1980) which requires the success of a policy to be seen from two dimensions, namely the content of the policy and the context of implementation. The data obtained were analyzed using a descriptive research method with a qualitative approach with data collection techniques, namely interviews, observation, and documentation. The results of the study indicate that the implementation of the job equivalency policy at the BSKDN Kemendagri has generally been carried out well, but is still less than optimal because the hierarchical structural work pattern and organizational culture are still thick with the structural system. The efforts of BSKDN are to disseminate information and encourage the commitment of leaders to participate in the implementation process, so that employees have clear guidance in carrying out tasks under the work culture after the equivalency into functional positions.